Associations between household air pollution and reduced lung function in women and children in rural southern India. Issue 11 (25th July 2018) - Patel, Sameer; Leavey, Anna; Sheshadri, Ajay; Kumar, Praveen; Kandikuppa, Sandeep; Tarsi, Jaime; Mukhopadhyay, Krishnendu; Johnson, Priscilla; Balakrishnan, Kalpana; Schechtman, Kenneth B.; Castro, Mario; Yadama, Gautam; et al.
Abstract: Half of the world's population still relies on solid fuels to fulfill its energy needs for cooking and space heating, leading to high levels of household air pollution (HAP), adversely affecting human health and the environment. A cross‐sectional cohort study was conducted to investigate any associations between: (1) HAP metrics (mass concentration of particulate matter of aerodynamic size less than 2.5 μm (PM2.5 ), lung‐deposited surface area (LDSA) and carbon monoxide (CO)); (2) a range of household and socio‐demographic characteristics; and (3) lung function for women and children exposed daily to biomass cookstove emissions, in rural southern India. HAP measurements were collected inside the kitchen of 96 households, and pulmonary function tests were performed for the women and child in each enrolled household. Detailed questionnaires captured household characteristics, health histories and various socio‐demographic parameters. Simple linear and logistic regression analysis was performed to examine possible associations between the HAP metrics, lung function and all household/socio‐demographic variables. Obstructive lung defects (forced vital capacity (FVC) ≥ lower limit of normal (LLN) and forced expiratory volume in 1 second (FEV1 )/FVC < LLN) were found in 8% of mothers and 9% of children, and restrictive defects (FVC < LLN and FEV1 /FVC ≥ LLN) were found in 17% of mothers and 15% of children. A positive association between LDSA, included for the first time in this type of epidemiological study, and lung function was observed, indicating LDSA is a superior metric compared to PM2.5 to assess effects of PM on lung function. HAP demonstrated a moderate association with subnormal lung function in children. The results emphasize the need to look beyond mass‐based PM metrics to assess fully the association between HAP and lung function. Abstract : Emissions from solid fuel cookstoves adversely affect human health and the environment. A cross‐sectional cohort study investigated associations between household air pollution metrics (PM2.5, lung‐deposited surface area (LDSA) and carbon monoxide), household and socio‐demographic characteristics, and lung function for women and children in households using a biomass cookstove, in rural southern India. A positive association between LDSA, included for the first time in this type of epidemiological study, and lung function indicates LDSA is a superior metric compared to PM2.5 to assess the effects of PM on lung function.